"Terror birds" (Phorusrhacidae) from the Eocene of Europe imply trans-Tethys dispersal. - Delphine Angst (Public Library of Science (PLoS), 2013)
Background Phorusrhacidae was a clade including middle-sized to giant terrestrial carnivorous birds, known mainly from the Cenozoic of South America, but also occurring in the Plio-Pleistocene of North America and the Eocene of Africa. Previous reports of small phorusrhacids in the Paleogene of Europe have been dismissed as based on non-phorusrhacid material. Methodology we have re-examined specimens of large terrestrial birds from the Eocene (late Lutetian) of France and Switzerland previously referred to gastornithids and ratites and have identified them as belonging to a phorusrhacid for which the name Eleutherornis cotei should be used. Conclusions/significance The occurrence of a phorusrhacid in the late Lutetian of Europe indicates that these flightless birds had a wider geographical distribution than previously recognized. The likeliest interpretation is that they dispersed from Africa, where the group is known in the Eocene, which implies crossing the Tethys Sea. The Early Tertiary distribution of phorusrhacids can be best explained by transoceanic dispersal, across both the South Atlantic and the Tethys.